Effect of Follow-up Telephone by Enterostomal Nurses on Patients with Permanent Colostomy: A Systematic Review (Bangladesh Journal of Medical Science, 2022)
Background: Patients with permanent colostomy experience quality of life (QoL) decrease, complications, and colostomy adjustment problems. Technology-based interventions can be provided with telephone follow-up (TFU) to provide health education and advice on managing symptoms, identifying complications, and providing quality care services.Objective: To systematically describe and assess the effect of TFU on permanent colostomy include population, model and duration, instruments used, and effect of TFU.Materials and Methods: A systematic review was carried out using the Randomized Controlled Trial (RCT) approach in eight databases, including PubMed, Proquest, ScienceDirect, EBSCOhost, CANCERLIT, Wiley, Gray literature, and Scopus, to identify studies reported in English, published in the last ten years, available full text, and about TFU in permanent colostomy patients.Results and Discussion: Based on the 11 RCT articles analyzed, it was found that the TFU duration ranged from 27 days to 3 years. The TFU improved self-efficacy, QoL, colostomy adjustment, self-care, self-management, service satisfaction, and complications.Conclusion: The TFU has more effect on self-efficacy, QoL, and complications in patients with a permanent colostomy, and effective TFU was performed for at least three months. Further research is needed on the frequency or duration of telephone calls.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 54-66